Vision of Society in George Orwell’s Fictional Works: A Critique of Oppression and the Quest for Social Justice in George Orwell's Fictional Works (Journal of Advances and Scholarly Researches in Allied Education, 2017)
George Orwell is one of the prominent and towering personalities among the twentieth century novelists who strongly plead for the down-trodden and oppressed classes in the society. He presents the reality of the contemporary society by exposing the totalitarian and authoritarian powers that sap the freedom and liberty of individuals. He experimented with various ideologies and set-ups like capitalism and imperialism, but concluded socialism as the only remedy for the intolerable conditions he explored in his fictional and non-fictional works. In his novels, one finds his protagonists fighting against tyranny, injustice, oppression and inequality.